2016
DOI: 10.5206/cjsotl-rcacea.2016.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Use of Lecture Capture Technology: Implications for Teaching and Learning

Abstract: This study sought to provide a better understanding of how lecture capture technology is used by students and how its use is related to student satisfaction, attendance, and academic performance. Using a mixed method design with both quantitative and qualitative methods to collect data, instruments included a student questionnaire, interviews and focus groups, lecture capture usage statistics, and grades. Results showed that 63% of students were satisfied with lecture capture and 75% of students indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 23 publications
8
44
1
Order By: Relevance
“…Given how and when lecture capture is used, studies have investigated its relationship to academic performance. This research shows that whilst students believe lecture capture positively impacts on performance (Al-Nashash & Gunn, 2013;Groen et al, 2016) studies using actual grades give a mixed picture with some indicating a positive relationship (Bollmeier, Wenger, & Forinash, 2010;Francom, Ryan, & Kariuki, 2011;Griffin, Mitchell, & Thompson, 2009;Harrigan, 1995;McFarlin, 2008;McKinney, Dyck, & Luber, 2009;Vajoczki, Watt, Marquis, & Holshausen, 2010;Wiese & Newton, 2013;Yu, Wang, & Su, 2015) and others reporting little or no relationship between the capture and performance (Abt & Barry, 2007;Brotherton & Abowd, 2004;Edwards & Clinton, 2019;Hadgu, Huynh, & Gopalan, 2016). These mixed findings may arise from differences in the populations sampled because student characteristics are known to influence use of capture.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Given how and when lecture capture is used, studies have investigated its relationship to academic performance. This research shows that whilst students believe lecture capture positively impacts on performance (Al-Nashash & Gunn, 2013;Groen et al, 2016) studies using actual grades give a mixed picture with some indicating a positive relationship (Bollmeier, Wenger, & Forinash, 2010;Francom, Ryan, & Kariuki, 2011;Griffin, Mitchell, & Thompson, 2009;Harrigan, 1995;McFarlin, 2008;McKinney, Dyck, & Luber, 2009;Vajoczki, Watt, Marquis, & Holshausen, 2010;Wiese & Newton, 2013;Yu, Wang, & Su, 2015) and others reporting little or no relationship between the capture and performance (Abt & Barry, 2007;Brotherton & Abowd, 2004;Edwards & Clinton, 2019;Hadgu, Huynh, & Gopalan, 2016). These mixed findings may arise from differences in the populations sampled because student characteristics are known to influence use of capture.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have shown that use of capture peaks during assessment and revision periods (Brady, Wong, & Newton, 2013;Gosper et al, 2010;Saunders & Hutt, 2015) and investigations into how lecture capture is used show that students use it to review complex material, revisit sections they missed in the live lecture (Gorissen, Van Bruggen, & Jochems, 2012;Gosper et al, 2010;Groen, Quigley, & Herry, 2016;Watt et al, 2014), make more detailed notes (Elliott & Neal, 2016;Gosper et al, 2010;Newton, Tucker, Dawson, & Currie, 2014;Saunders & Hutt, 2015;Watt et al, 2014) and take control over their learning, particularly through self-pacing (Al-Nashash & Gunn, 2013;Gosper et al, 2010;Newton et al, 2014;Watt et al, 2014). Perhaps unsurprisingly, the use of lecture capture appears most beneficial where the student has English as a second language or there is otherwise a difference in first language between the student and lecturer (Gosper et al, 2010;Groen et al, 2016;Revell, 2013;Saunders & Hutt, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research into lecture capture has consistently found that students have a positive perception of capture (Gosper et al 2008;O'Callaghan et al 2017;Pons et al 2012;Traphagan et al 2010). Studies show higher usage of captured lectures during assessment (Brady et al 2013) and revision periods (Gosper et al 2010;Saunders and Hutt 2015), with students using it to review complex material, pick up on sections they missed in the live lecture (Gorissen et al 2012;Gosper et al 2010;Groen et al 2016), make more detailed notes (Elliott and Neal 2016;Gosper et al 2010;Newton et al 2014) and take control of their learning, particularly through self-pacing (Al-Nashash and Gunn 2013;Gosper et al 2010;Newton et al 2014;Watt et al 2014). Other research indicates that students believe lecture capture improves their performance because they are able to review difficult sections and revisit the material as often as needed (Al-Nashash and Gunn 2013; Groen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show higher usage of captured lectures during assessment (Brady et al 2013) and revision periods (Gosper et al 2010;Saunders and Hutt 2015), with students using it to review complex material, pick up on sections they missed in the live lecture (Gorissen et al 2012;Gosper et al 2010;Groen et al 2016), make more detailed notes (Elliott and Neal 2016;Gosper et al 2010;Newton et al 2014) and take control of their learning, particularly through self-pacing (Al-Nashash and Gunn 2013;Gosper et al 2010;Newton et al 2014;Watt et al 2014). Other research indicates that students believe lecture capture improves their performance because they are able to review difficult sections and revisit the material as often as needed (Al-Nashash and Gunn 2013; Groen et al 2016). However, studies using actual grades show a mixed picture, with some indicating a positive relationship between lecture capture availability/use and actual grades (Bollmeier et al 2010;Francom et al 2011; Wiese and Newton 2013;Yu et al 2015) and others reporting little or no relationship between the two (Abt and Barry 2007;Brotherton and Abowd 2004;Edwards and Clinton 2018;Hadgu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of universities in the UK and beyond have extended their capacity for lecture capture in recent years, and lecturers are encouraged (and in some institutions, obliged) to make use of the technology (Newland, 2017). The benefits cited include: convenience and flexibility for students; the ability to provide additional and archived resources; the ability to allow students with different learning styles to learn at 5 their own pace; enhancing engagement in lectures by providing students security that they can listen rather than take detailed notes; help students revise for exams and prepare for coursework; allow active learning in seminars by enabling students to revise lectures before a seminar meeting; and, allow students who miss classes to catch up (Davis, Connolly, & Linfield, 2009;Groen et al, 2016;Traphagan et al, 2009). Students increasingly expect to be able to use online learning to supplement or even replace lecture attendance, despite the questionable pedagogic rational (Holbrook & Dupont, 2009).…”
Section: Technologymentioning
confidence: 99%